Persepsi Siswa terhadap Keterampilan Mengajar Guru Sejarah di SMK TI Labbaika Samarinda - Mira Amalia; Sainal A; Muhamad Sopyan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Study This aiming For know How perception student to skills teaching history teacher at SMK TI Labbaika Samarinda , type research used that is Qualitative descriptive with technique observation data collection , interviews And documentation , focus study focus on perception student onskills open And closing skills manage class , skills explain , skills give strengthening , skills ask , skills guide group , skills stage variations. Results study show that perception student about skills teaching teachers, has in accordance with skill indicators teach teacher. History teachers are rated capable convey material with clear in manage class with Good give strengthening And motivation to student as well as create atmosphere learning is fun , but There is things that need to be fixed on skills stage variations of learning media used , there are Lots media types and methods that can used in the learning process of history teachers can using different media different for students No fed up And bored during the learning process.